Testing the excavator performance (using Topcon 3d Excavator X63 System) especially for navigation and earthwork - Pırtı, Atınç; Yazici, Muharrem; Yucel, Mehmet Ali (Geodesy and Cartography, 2023)
Construction sites commonly utilize bulldozers, wheel loaders, excavators, scrapers, and graders. Among these, excavators are versatile hydraulic heavy-duty equipment operated by humans. They are employed for various tasks like digging, levelling the ground, transporting and dumping loads, as well as providing straight traction. However, certain hazardous environments, such as nuclear disasters or earthquakes, are not suitable for human on-site work. To enhance productivity, accuracy, and profitability in excavation projects, the adoption of 3D machine control is recommended. The Topcon 3D Excavator X63 System offers advanced and precise GNSS positioning technology, coupled with Hidromek with Assist and an intuitive software interface, to significantly improve excavation operations. In this study, the accuracy of the coordinates of the route followed by the Excavator was checked by using RTK GNSS method by using P1 reference point. While the differences obtained in horizontal coordinates are 2–2.5 cm and 4–6 cm in vertical coordinates. In addition, excavation calculations of the earthwork area were performed and checked with the number of bucket of the excavator. The differences obtained from the earthwork were calculated as 0.8 cubic meters for each bucket.